Effect of Borax as Source of Boron in the Characteristics of Grape (Visit vinifera L) Cultivar Blank monika. - Mahdy, I. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A study was carried out in the vineyard at Al- sowayra in the Waset Province to study the effect of boron spray on cluster and fruits traits characteristics of grape cultivar . Borax used  was as a source of boron at the concentrations (0.0 , 0.1, 0.2, 0.3, 0.4 and 0.5 ) g / l . Water plus Wetting agent   (0.05 g/l detergent) was sprayed to induce faom and reduce water surface tension. The spray was implemented twice, first was one week before blooming and the second was after fruit set. Results showed that spray treatment by boron increased. weight and volume of berries and increased cluster's weight bunch length and diameter besides the increased number of Fruits in bunch also Total Soluble Solids (Tss%) was increased while total acidity was decreased by borax spray . The number and weight of seed increased by boron treatment. The concentration 0.05 g/l had a greater effect on all the studied characters .  Randomized compete block design was used, the number of total which used in study was 18 vines where each vine represented an experimental unit adopted with three replicates Results was analysied by (4) used LSD test in 0.05 leves to compare between means.